THE UNBIASED TRUTH ABOUT ARTIFICIAL SWEETENERS - CHAUDHARY, SUSHIM (International Journal of Clinical and Biomedical Research, 2016)
Sugar contribute to tooth decay and obesity but still we spoon it. Artificial sweeteners are used in one of two ways. They may be used directly in commercially processed foods or they are mixed with one or more starch based sweeteners before sale to consumers. Artificial sweeteners are so intensely sweet so small Amounts are required to imitate sugars sweet taste. In this review paper, it is going to discuss about the basic five Artificial sweeteners like Aspartame, Acesulfame, Saccharin, Sucralose and Neotame.